Sensitivity analysis of the effects of load magnitude on pavement strains using load spectra - Murana, A. A.; Olowosulu, A. T.; Awosanya, D. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The purpose of this study is to evaluate the effect of wheel loads on linear responses by sensitivity analysis on an elastic linear analysis. Sensitivity analysis of traffic factors was carried out on the failure parameters, where the impact of each of the wheel load magnitude for each axle type and its relationship with the pavement response outputs was evaluated. The reference central value (mean) of the ALS on both the southbound axis and northbound axis of the selected route, Kaduna-Zaria roadway, were either increased or reduced by 0% to 50%, and also, 100% and 500%, to see how the pavement will respond to a constant pavement configuration and material properties applied to all cases. The results obtained from KENLAYER runs were used to determine the relationship between the axle load groups and the pavement responses. The effect of load magnitude on pavement responses, was evaluated in respect of the tensile strains and compressive strains. The findings of the study revealed that: Development of comprehensive data base was accomplished from the local traffic data that meets the requirements of M-E design procedure. Wheel load group relationship for each axle type to vertical strains on top of the subgrade soils are linear, while the tensile strain at the bottom of the asphalt concrete is about 50%.